Global well-posedness for the 2D MHD-Boussinesq system with temperature-dependent diffusion. (August 2020) - Yu, Yanghai; Fei, Mingwen
Abstract: In this paper, we aim at extending the global existence results given by Abidi–Zhang (2017) and Zhai–Dong–Chen (2019), who considered the 2D Boussinesq system with the critical dissipation for α = 1 2 and the supercritical dissipation for α ∈ ( 1 3, 1 2 ], respectively, to the MHD-Boussinesq system with supercritical temperature dissipation for α ∈ ( 0, 1 2 ) .